Correction: Utilization of urea and expression profiles of related genes in the dinoflagellate Prorocentrum donghaiense. - Xiaoli Jing; Senjie Lin; Huan Zhang; Claudia Koerting; Zhigang Yu (PLoS ONE, 2018)
[This corrects the article DOI: 10.1371/journal.pone.0187837.].